'A Taster of Political Insult': The Case of Novi Sad's Youth Tribune, 1968–1971. Issue 4 (4th July 2018) - Ilić, Marko
Abstract: In the former Yugoslavia, Students' Cultural Centres played host to the conceptual and performance art scenes that came to be known as the 'New Art Practice', fostered under the political programme of socialist self-management. This article traces a specific episode in the history of Novi Sad's Youth Tribune, when the city's New Art Practices crossed into political engagement and provocation. I follow the increased bureaucratisation of the Youth Tribune – the resistance to it, and the coercive consequences – along with the ultimate dilution of radical practices in Novi Sad, that forced its key players to appeal to an 'Invisible Art'. Though Yugoslavia is frequently characterised as a country which encouraged public debate, the unique and important case of Novi Sad reveals the consequences of a direct confrontation with the city's cultural apparatus, at a moment marked by oppressive change and political turmoil.